KESEIMBANGAN LINGKUNGAN ANTARA KEBUTUHAN DAN PENYEDIAAN AIR MELALUI TEKNOLOGI MODIFIKASI CUACA - Ch Nasution (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
The process of weather modification to increase rainfall amount can be donecontinuously when the weather condition is favorable and can be used to maintain DAM water level especially during the dry season. By maintaining the DAM water level with the weather modification technology the environmental balance between supply and demand will be sustained. To reduce the rainfall intensity in order to lessen the impact of flood with the weather modification technology by early precipitation, which eventually lessen the intensity and the accumulated rainfall amount. The application of the weather modification technology to clear the atmosphere due to the forest fire and land clearing activities can be used to area where fires is still ongoing. The use of that technology not only clears the atmosphere but also allows convection processes to happen because the cloud development was hindered by thick smoke from fires.